Meghadūta inaczej. Zderzenie idealizmu z realizmem w dramacieRakesia Āṣāṛh kā ek din - Miążek, Teresa (Gajt Wydawnictwo 1991 s.c., 2018)
The paper deals with Mohan Rākeś’s usage of Meghadūtā as a motif in his drama Āṣāṛh kā ek din of 1958. Introducing the atmosphere of this famous work by Kālidāsa, the writer quotes from it at the very beginning of his play, and he also gives his hero the name of this Sanskrit poet. In Rākeś’s work, Meghadūtā symbolises all Kālidāsa’s plays and poems and his idealistic approach to heroes and their love relations, which Rākeś consequently contests in the next two acts of his play. This is a way of presenting his modern ideas on the development of Hindi dramatic art. Making such references to Sanskrit kāvya literature, the writer creates a solid background which he uses as a contrast to his own innovations in drama, both in terms of themes and techniques, such as: a story of unfulfilled love, the portrayal of the male character as weak and indecisive, the leading role of the heroine, her key role in the development of the action, and the tragic end of the play. The genius of K ālidāsa’s poetry reemployed by Rākeś in his modern Hindi play produces a two-way effect: on the one hand it reinforces the position of this Hindi dramatist, and on the other finds a new and productive context in which it appears fresh and beautiful. The success of Rākeś’s play lies in its highly sanskritised style, which reflects the atmosphere of the golden age of Sanskrit kāvya.
Keywords: Mohan Rākeś; Meghadūta